EFFECT OF BIOFUMIGATION ON POTATO CYST NEMATODES - Umamaheswari, R; Bairwa, Aarti; Venkatasalam, E P; Sudha, R; Singh, B P (Potato Journal, 2016)
Potato cyst nematodes (PCN) Globodera rostochiensis (Woll) and G. pallida (Stone) hinder the sustainable production of potato in the Nilgiri hills of Tamil Nadu. It remains as a serious endemic pest of potato in this region due to intensive cultivation of potato and favourable climatic conditions. Hence, field experiments were conducted to evaluate the efficacy of bio-fumigation by incorporating chopped residues of radish, cabbage and cauliflower in potato cv. Kufri Giriraj. One set of treatments were covered with transparent polyethylene sheets for 4 weeks before planting and another set was left uncovered. The biofumigants were compared with the chemical nematicide carbofuran @ 2 kg a.i /ha. The treatments were replicated thrice in a randomized block design. The results revealed that all the treatments significantly increased the potato yield and decreased the nematode population. Incorporation of radish leaves @ 1 kg/m2 and covering with polyethylene sheet recorded maximum growth parameters, yield (25.97 t/ha) and minimum PCN reproduction factor (Rf) 1.21. It was on par with carbofuran treatment which yielded 25.09 t/ha and PCN reproduction factor (Rf) 1.24 and was followed by cabbage and cauliflower residues covered with polyethylene sheet.